Gender Discrimination in the Allocation of Migrant Household Resources - Francisca M. Antman (Institute for the Study of Labor (IZA), 2015)
This paper considers the relationship between international migration and gender discrimination through the lens of decision-making power over intrahousehold resource allocation. The endogeneity of migration is addressed with a difference-in-differences style identification strategy and a model with household fixed effects. The results suggest that while a migrant household head is away, a greater share of resources is spent on girls relative to boys and his spouse commands greater decision-making power. Once the head returns home, however, a greater share of resources goes to boys and there is suggestive evidence of greater authority for the head of household.
Keywords: O15; F22; D13; J16; 330; migration; intrahousehold allocation; gender discrimination; education; bargaining power